HUBUNGAN TINGKAT STRES AKADEMIK DENGAN SISTEM PERKULIAHAN JARAK JAUH BERBASIS ONLINE TERHADAP KUALITAS TIDUR MAHASISWA TAHUN PERTAMA - Zafira Firstika; Darwin Karim; Rismadefi Woferst (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2020)
Introduction: Stress can affect sleep quality. This study aims to look at the relationship between academic stress levels and online-based distance lecturing systems on the sleep quality of first-year students. Methods: The descriptive correlation study design used a cross-sectional approach. Sample 107 respondents, sampling simple random sampling. The analysis used univariate analysis to see the frequency distribution and bivariate using the Chi-Square test. Results: The majority of respondents from program A 2019 1 were 58 (55.1%). The majority of respondents aged 19 years were 65 (60.7%). The majority of the respondent's sex is female as much as 93 (86.9%). The majority of respondents' achievement index (IP) was 2.76-3.50 (very satisfying) as many as 84 (78.5%). The results showed that respondents with severe academic stress levels, 49 respondents (51.9%) experienced poor sleep quality, while 42 respondents (39.1%) had poor sleep quality. The statistical test results obtained p-value = 0.193> α (0.05), which means that Ho failed to be rejected, it can be concluded that there is no relationship between the level of academic stress and the online-based distance lecture system on the sleep quality of first-year students. Conclusion: The results of this study are expected to be an input for educational institutions as a source of information in efforts to prevent stress and poor sleep quality disorders in students.Keywords: Academic stress level, distance lecture system, sleep quality